A Content Analysis of Intake Paperwork: An Exploration of How Clinicians Ask About Gender, Sex, and Sexual/Affectual Orientation. Issue Volume 12:Issues 2(2018) (3rd April 2018) - Skaistis, Shannon M.; Cook, Jennifer M.; Nair, Dhanya; Borden, Sydney
ABSTRACT: In the United States, the transgender and gender nonconforming (TGNC) population has increased twofold since 2011. Although counseling professionals are called to provide competent services to TGNC clients, no empirical studies exist that examine one of the first points of contact: Intake paperwork. The authors conducted a content analysis (N = 128) of intake paperwork and assessed how and if clinicians asked for gender, sex, and sexual/affectual orientation, and whether they conflated these constructs. Findings indicate adjustments need to be made for intakes to be more inclusive of these constructs. The authors offer clinical implications and avenues for future research.